Responses of Fungi Maggot (Bradysia impatiens Johannsen) to Allyl Isothiocyanate and High CO2 - Gou, Yu-Ping; Quandahor, Peter; Mao, Liang; Li, Chun-Chun; Zhou, Jing-Jiang; Liu, Chang-Zhong (Frontiers in Physiology, 2022)
Botanical pesticide is highly recommended for integrated pest management (IPM), due to its merits such as environmental friendliness, safe to non-target organisms, operators, animals, and food consumers. The experiment was conducted to determine the lethal and sub-lethal effects of allyl isothiocyanate (AITC) on eggs, third instar larvae, pupae, and females and males of Bradysia impatiens Johannsen (B. impatiens). Different concentrations of AITC under ambient CO2 by the conical flask sealed fumigation method were used for the experiment. The results showed that there was a significant linear relationship between different concentrations of AITC and the toxicity regression equation of B. impatiens. The sub-lethal concentrations of AITC had significant effects on the larval stage, pupal stage, pupation rate, pupal weight, adult emergence rate, and oviposition. The pupation rate, pupal weight, and adult emergency rate were significantly (p < 0.05) affected by AITC fumigation. The pupation rate was the lowest after fumigation treatment of AITC at LC50 (36.67%), followed by LC25 (41.94%), compared with the CK (81.39%). Female longevity was significantly (p < 0.05) shortened by fumigation at LC25 (1.75 d) and LC50 (1.64 d), compared with that of CK (2.94 d). Male longevity was shorter at LC25 (1.56 d) than at LC50 (1.25 d) and had no significant difference between these two treatments. The fumigation efficiency of AITC was significantly increased under high CO2 condition. Furthermore, detoxification enzyme activities and antioxidant enzyme activities were accumulated under high CO2 condition. The fumigation method in the application of AITC can be useful in areas where B. impatiens is a major concern.